2017
DOI: 10.1093/neuonc/nox097
|View full text |Cite
|
Sign up to set email alerts
|

Soluble TACI and soluble BCMA as biomarkers in primary central nervous system lymphoma

Abstract: Our results suggest that sTACI and sBCMA in the CSF are promising new biomarkers for diagnosis and therapy monitoring in PCNSL. However, our findings need to be validated in an independent cohort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 33 publications
2
29
0
Order By: Relevance
“…The diagnostic values of markers, as derived from the included studies, are listed for PCNSL (Table ) (Kersten et al , ; Murase et al , ; Roy et al , ; Baraniskin et al , , , ; Sasayama et al , ; Rubenstein et al , ; Mao et al , ; Kuusisto et al , ; Sasagawa et al , ; Viaccoz et al , ; Mabray et al , ; Nguyen‐Them et al , ; Song et al , ; Strehlow et al , ; Ikeguchi et al , ; Thaler et al , ) and for SCNSL (Table ) (Ernerudh et al , ; Kersten et al , ; Kara et al , ; Muñiz et al , ). Some of the included articles reported the diagnostic values for PCNSL and SCNSL as one patient group (Roy et al , ), these results are also included in Table .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The diagnostic values of markers, as derived from the included studies, are listed for PCNSL (Table ) (Kersten et al , ; Murase et al , ; Roy et al , ; Baraniskin et al , , , ; Sasayama et al , ; Rubenstein et al , ; Mao et al , ; Kuusisto et al , ; Sasagawa et al , ; Viaccoz et al , ; Mabray et al , ; Nguyen‐Them et al , ; Song et al , ; Strehlow et al , ; Ikeguchi et al , ; Thaler et al , ) and for SCNSL (Table ) (Ernerudh et al , ; Kersten et al , ; Kara et al , ; Muñiz et al , ). Some of the included articles reported the diagnostic values for PCNSL and SCNSL as one patient group (Roy et al , ), these results are also included in Table .…”
Section: Resultsmentioning
confidence: 99%
“…Transmembrane activator and calcium modulator and cyclophilin ligand interactor (TACI) and B cell maturation antigen (BCMA) are receptors involved in the B cell homeostasis system. It was recently demonstrated that both receptors also exist in a soluble form (Thaler et al , ). A recent study on PCNSL patients described superior diagnostic value of sTACI over sBCMA in CSF (Thaler et al , ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1 Thaler et al reported that CSF and serum TACI and BCMA levels were higher in patients with PCNSL than in control patients. 7 The present study aimed to evaluate the possibility that CSF and serum levels of BAFF and TACI could be diagnostic biomarkers specific for PCNSL rather than glioblastoma and inflammatory or autoimmune CNS diseases.…”
Section: Introductionmentioning
confidence: 99%